Does Financial Institution Support for Economic Growth? A Case of Nepal - Dhungana, Bharat Ram (Economic Literature, 2016)
This paper examines the causality of economic growth and financial institutions with reference to Nepalese economy and determines whether financial institutions supports for economic growth or not. The empirical analysis shows that there is existence of long run association among the variables of gross domestic product (GDP), broad money (M2) and domestic credit to private sectors (DCPS). Moreover, vector error correction model (VECM) also suggests for the validity of the long run association among variables. The Granger causality and Wald statistics test do not find any short run causal relationship. The empirical result shows that there is a long-run association between financial institutions and economic growth of Nepal. Thus, a sound financial system helps to promote financial institutions in the country that supports for economic growth of the nation in the long run. The regulatory authority and financial institutions should accelerate financial reforms to improve the efficiency of financial system that helps to stimulate adequate capital formation and investment in the productive sectors.Economic Literature Vol.12 2014: 56-68